1989
DOI: 10.1128/jb.171.12.6414-6422.1989
|View full text |Cite
|
Sign up to set email alerts
|

Proteus mirabilis urease: nucleotide sequence determination and comparison with jack bean urease

Abstract: Proteus mirabilis, a common cause of urinary tract infection, produces a potent urease that hydrolyzes urea to NH3 and C02, initiating kidney stone formation. Urease genes, which were localized to a 7.6-kilobase-pair region of DNA, were sequenced by using the dideoxy method. Six open reading frames were found within a region of 4,952 base pairs which were predicted to encode polypeptides of 31.0 (ureD), 11.0 (ureA), 12.2 (ureB), 61.0 (ureC), 17.9 (ureE), and 23.0 (ureF) kilodaltons (kDa). Each open reading fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
110
0
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(114 citation statements)
references
References 34 publications
3
110
0
1
Order By: Relevance
“…No precise role can be attributed to the UreC-predicted polypeptide in the absence of similarities between its'amino acid sequence and that of the identified UreD, UreE, or UreF polypeptide of the P. mirabilis urease operon (23,32). These polypeptides are believed to be involved in the processing of nickel ions and/or transport of the urea from the extracellular to the intracellular compartment (32).…”
Section: Resultsmentioning
confidence: 99%
“…No precise role can be attributed to the UreC-predicted polypeptide in the absence of similarities between its'amino acid sequence and that of the identified UreD, UreE, or UreF polypeptide of the P. mirabilis urease operon (23,32). These polypeptides are believed to be involved in the processing of nickel ions and/or transport of the urea from the extracellular to the intracellular compartment (32).…”
Section: Resultsmentioning
confidence: 99%
“…To determine that this polypeptide was UreE, the purified protein was subjected to N-terminal amino acid analysis. Comparison of the first 10 amino acids of the purified protein (Met-Lys-Lys-Phe-Thr-Gln-Ile-Ile-Asp-Gln) with that of the amino acid sequence of P. mirabilis UreE predicted from the nucleotide sequence (16) weight range, 3,000 to 70,000). The protein eluted at 22 min as measured by the relative A280, corresponding to an apparent molecular size of 36 kDa.…”
Section: Resultsmentioning
confidence: 99%
“…Urease genes of P. mirabilis have been cloned (15) and sequenced (16,28,32), and deletion mutations have been constructed (10,32). In the course of these studies, we observed that clones lacking ureE, ureF, or ureG (accessory genes in the P. mirabilis urease gene cluster) do not express catalytically active urease in unsupplemented medium.…”
mentioning
confidence: 99%
“…The region encoding this set of genes was found to be located immediately downstream of the four genes, ureC, ureD, ureA, and ureB, previously described (16). It consisted of a 3.2-kb fragment having five ORFs which were designated (according to the nomenclature used for K aerogenes [26] and Proteus mirabilis [14]) ureI, ureE, ureF, ureG, and ureH.…”
Section: Materuils and Methodsmentioning
confidence: 99%